Tantangan Manajemen Pembelajaran Berbasis Personalized Learning: Tinjauan Literature Review - Lusiana, Lufita; Rugaiyah, Rugaiyah; Zulaikha, Siti; Mayasari, Linda Ika; Takdir, Muhammad (Proceeding of Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2025)
This study aims to identify managerial challenges in implementing personalized learning in Indonesian schools. Using a Systematic Literature Review (SLR) approach with PRISMA guidelines, a literature search was conducted based on the Google Scholar database in 2020–2025. Of the 192 initial articles, 23 articles met the inclusion criteria and were analyzed thematically. The results revealed three main challenges: (1) weak strategic planning and institutional policies, (2) limited teacher capacity in pedagogical, digital, and analytical competencies, as well as high workloads, and (3) uneven distribution of digital infrastructure and technological support. These findings suggest that the success of personalized learning depends on systemic transformation of school management, not just pedagogical innovation. The study recommends transforming school management through the development of personalization policies, ongoing training, redistribution of teacher tasks, and investment in digital infrastructure.